2021
DOI: 10.1186/s12905-021-01556-2
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of Polish women’s level of knowledge about endometriosis: a pilot study

Abstract: Introduction Insufficient knowledge about endometriosis among women is one of the causes of its delayed diagnoses. Due to the elusiveness of symptoms, the most important component of early detection is proper and exhaustive knowledge. The objective of the study was to assess Polish women's awareness of endometriosis. Methods The pilot studies were performed with the participation of 200 women, in an average age of 33.65 years (SD = 11.45), who comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…3, The Correlations between Knowledge and Education Levels, the p-value > 0.05 means there is no relationship between education level and knowledge of endometriosis, This study agree with many previous study as (Kotowska et al, 2021), (Adewunmi & Sasah, 2022. ), (Arab et al, 2022), (Henry et al, 2022), (Kotowska et al, 2021), (Le Busque & Mellish, 2023), (S. L. Mohamed El Sayed et al, 2022), (Ramani Devi et al, 2021, (Roullier et al, 2021), (Szymańska & Dąbrowska-Galas, 2021), (Wróbel et al, 2022), (Khan et al, 2022), (Sodeinde & Konu, 2022), (Randhawa et al, 2021), (Henry et al, 2022), (Navarria-Forney et al, 2020), (Mohamed & Hassan, 2020. ), (Mecha et al, 2022), (Eldardery et al, 2022), (Abd Elrahim et al, 2022), (Adewunmi & Sasah, 2022.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, The Correlations between Knowledge and Education Levels, the p-value > 0.05 means there is no relationship between education level and knowledge of endometriosis, This study agree with many previous study as (Kotowska et al, 2021), (Adewunmi & Sasah, 2022. ), (Arab et al, 2022), (Henry et al, 2022), (Kotowska et al, 2021), (Le Busque & Mellish, 2023), (S. L. Mohamed El Sayed et al, 2022), (Ramani Devi et al, 2021, (Roullier et al, 2021), (Szymańska & Dąbrowska-Galas, 2021), (Wróbel et al, 2022), (Khan et al, 2022), (Sodeinde & Konu, 2022), (Randhawa et al, 2021), (Henry et al, 2022), (Navarria-Forney et al, 2020), (Mohamed & Hassan, 2020. ), (Mecha et al, 2022), (Eldardery et al, 2022), (Abd Elrahim et al, 2022), (Adewunmi & Sasah, 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the elusiveness of symptoms, the most important component of early detection is proper and exhaustive knowledge. (Szymańska & Dąbrowska-Galas, 2021). Awareness of the possibility of developing the disease in a particular patient, combined with appropriate use of ultrasound examination, can contribute to the decrease in diagnostic delay.…”
Section: Introductionmentioning
confidence: 99%
“…However, the level of knowledge about endometriosis among women is insufficient, which may have an impact on the failure to see a specialist and thus delay the diagnosis of the disease and the initiation of treatment [44]. Although endometriosis may affect as many as 176 million women around the world, we still know little about the disease, and its causes are still being sought [45].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have explored the knowledge of endometriosis in different populations. A study conducted by Szymańska et al in Poland found that 84% ( n = 200) of women had heard of endometriosis, whereas only 4.5% of them had very good knowledge [ 31 ]. Another study reported by Zanden et al in the Netherlands found that general practitioners (GPs) were not able to increasingly recognize endometriosis among patients, which lead to diagnostic delays [ 32 ].…”
Section: Discussionmentioning
confidence: 99%